Fostering Students' Self-Esteem in Speaking by Extending Speaking Activities in Social Media - Yosevina Rosdiana Su; Fatmawati Fatmawati (State Institute for Islamic Studies IAIN of Metro, 2019)
Speaking in foreign language involves both cognitive and psychological process which eventually bring it as the most challenging skill to learn. However, many learners do not have adequate opportunities to practice speaking unless in the classroom, thus, teachers and students needed to developed various extensive speaking activities including utilizing technological features such as social media. This study is aimed at describing the students' perceptions about extending speaking activities in social media and how it impacts on the improvement of their skill as well as their self-confidence in speaking. It was a case study involving 5 students of English Department in Universitas Katolik Indonesia Santu Paulus Ruteng, East Nusa Tenggara as the participants. The data were collected by observing the participants’ English-Speaking videos posted on Facebook and Focus Group Discussion. The observation sheet and the discussion guidelines were used as the instruments of data collection. To analyze the data, the researchers used Miles and Huberman’s procedures of data analysis, comprising: data reduction, data displaying, and conclusion drawing. This study revealed that extending the speaking activities in social media had positively enhanced the students’ speaking ability as well as their self-esteem in speaking.